2017
DOI: 10.1093/carcin/bgx130
|View full text |Cite
|
Sign up to set email alerts
|

HPV-negative, but not HPV-positive, oropharyngeal carcinomas induce fibroblasts to support tumour invasion through micro-environmental release of HGF and IL-6

Abstract: Human papillomavirus (HPV) infection is causally related to a subset of oropharyngeal carcinomas (OPC) and is linked to a more favourable prognosis compared to HPV-negative OPC. The mechanisms underlying this effect on prognosis are not fully understood, but interactions with the tumour microenvironment may be pivotal. Here, we investigated the role of the tumour microenvironment in HPV-positive compared to HPV-negative cancer using 2D and 3D modelling of OPC interactions with stromal fibroblasts. HPV-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…However, data relating to the nature of leukocyte‐recruiting chemokines released from HPV‐positive and HPV‐negative OPC is lacking. The tumour microenvironment involves crosstalk between cancer and stromal cells and this interaction appears to be crucial for many aspects of cancer progression . We therefore used a 2D in vitro model to examine HPV‐positive versus HPV‐negative cancer‐stromal interactions, and how such interactions may influence micro‐environmental chemokine release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, data relating to the nature of leukocyte‐recruiting chemokines released from HPV‐positive and HPV‐negative OPC is lacking. The tumour microenvironment involves crosstalk between cancer and stromal cells and this interaction appears to be crucial for many aspects of cancer progression . We therefore used a 2D in vitro model to examine HPV‐positive versus HPV‐negative cancer‐stromal interactions, and how such interactions may influence micro‐environmental chemokine release.…”
Section: Discussionmentioning
confidence: 99%
“…Although OPC cell lines are able to secrete a number of chemokines, there is increasing evidence that it is the crosstalk between tumour cells and stromal fibroblasts that is more important for cancer progression . We have recently demonstrated that HPV‐negative cancer cells drive the secretion of hepatocyte growth factor from oral fibroblasts which, in turn, influences tumour cell invasion; a mechanism that is reduced in response to HPV‐positive cells . It is therefore plausible that the chemotactic cues driven by the tumour microenvironment in HPV‐positive OPC is different from those in HPV‐negative OPC and this may account for differences observed in tumour‐associated leukocyte sub‐populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, and others, have provided evidence that cancer cells secrete cytokines and growth factors that mediate fibroblast activation into cancer associated fibroblasts (CAFs), which is considered an early and important event in tumourgenesis (25)(26)(27). To investigate whether the isolated CSCs signal differently to fibroblast we analysed expression of two genes commonly up-regulated in CAFs: α-SMA and IL-6 (28-31) upon exposure to condition media from isolated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The further conformational binding of HGF with the kinase domain of MET includes the activation of cascade events within the increasingly complex nature of oncogenesis. Human papillomavirusnegative oropharyngeal carcinomas enhance fibroblast-induced support of tumor invasion through microenvironmental release of HGF and IL-6 [3]. Primal attachment and also detachment dynamics of ligand-receptor binding allows a largely permissive nature for binding that is originally cooperative coordination in terms of collaborative instances in cell growth and cell scatter.…”
Section: Introductionmentioning
confidence: 99%